Learning to curate. Issue 6 (10th April 2015) - Doty, Jennifer; Herndon, Joel; Lyle, Jared; Stephenson, Libbie
Abstract : EDITOR'S SUMMARY Three data specialists reviewed their experiences learning about and applying the Inter‐university Consortium for Political and Social Research (ICPSR) processes and tools for curating research data. A small virtual community discussed curation theories on data acquisitions, review, processing, metadata and dissemination and shared progress implementing the ICPSR workflows and tools. Curators at Duke University, dealing with data on political donors, found processing obstacles from incomplete and mismatched data and faced confidentiality questions. At Emory University, gaps in coded data on home schooling practices revealed problems arising from lack of preplanning for long‐term archiving and research and the need to clarify data needs for later re‐use. By applying ICPSR processes, curators at UCLA's Social Sciences Data Archive were able to improve their workflow and understand the work necessary for open archiving. All participants gained from the opportunity to practice ICPSR curation practices, realized the resource demands and saw the value librarians can provide by consulting with faculty on data management and preservation.